Income Policies in the Light of International Experience : Further Comments - Sturmthal, Adolph (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1968)
It remains that the main problem of an incomes policy as a mean of restraining inflation in a full employment economy is that of the long run. It is, I believe, fair to point out that this problem has hardly been tackled so far and that the tendency to look at incomes policy in the light of temporary emergencies has blocked rather than opened the road to a solution.